Energy Budget of Clostera cupreata Butler (Lepidoptera: Notodontidae) on the Leaves of Poplar - Ahluwalia, Rajani (Indian Forester, 2012)
All the five larval stages of Clostera cupreata were fed and grown on the leaves of poplar and their energy budget was drawn. A linear increase in assimilation, consumption and tissue growth was found but an irregular trend of egestion in developing instars was observed.